Reconstructing Ötzi’s shoes - Eva IJsveld (EXARC Journal, 2023)
Ötzi the Gletshermummie, Ötzi the Iceman and Tisenjoch are the names we gave the man that walked in the Alps 5,300 years ago. Thanks to the Ötzi museum in Bozen/Bolzano, Italy, I had the opportunity to reconstruct Ötzi’s shoes. For making the shoes I used a flint knife, for both shoes I mostly used one knife. The net is made by hand so not many tools were needed to reconstruct the shoes. The book that has detailed information about Ötzi’s clothing is Kleidung und Ausrüstung der Kupferzeitlichen Gletschermumie aus den Ötztaler Alpen (Egg and Spindler, 2009). This book was my source of information for photos and reconstruction drawings as I planned to reconstruct the footwear worn by Ötzi. The drawings used a scale to determine the right size. In the reconstruction drawings from this book, I added the sizes and marked some areas for investigation. In the Ötzi museum in Bolzano we were able to take a good look at the ‘real thing and the museum provided us after the latest research data on the shoes.